Brown Tumour of Posterior Maxilla Associated with Polydactyly, Syndactyly and Cardiac Anomalies: A Unique Case Report - Suresh K V; Kumar Nilesh; Mounesh Kumar C D; Manisha R Patil; Pramod R C (Journal of Clinical and Diagnostic Research, 2014)
Brown tumour [BT] is an uncommon, non neoplastic complication of Hyperparathyroidism [HPT]. Skeletal changes are the main consequences of this endocrine condition. HPT manifest in three categories. Primary HPT is due to hyperfunction of one or more parathyroid gland, causing an increase of parathyroid hormone secretion resulting in hypercalcemia. Secondary HPT occurs due to chronic renal failure, decreased vitamin D production or with hypocalcemia. Tertiary HPT occurs when the parathyroid activity turns autonomous and excessive, leading to hypercalcemia. BT occurs frequently in the mandible than the maxilla. They are more common in women aged over 50y and majority of BT are asymptomatic. Radiographically, it appears as well defined radioluceny. The gross specimen usually shows a brown or reddish-brown colour. We report a relatively rare combination of maxillary posterior BT as a clinical manifestation of secondary HPT due to vitamin D deficiency with polydactyly, syndactyly and cardiac anomalies.